2013
DOI: 10.1063/1.4818274
|View full text |Cite
|
Sign up to set email alerts
|

Optical bistability in side-mode injection locked dual-mode Fabry-Pérot laser diode

Abstract: In this paper, optical bistability characteristics are demonstrated experimentally based on a dual-mode laser system comprising a multi-mode Fabry-Pérot laser diode (MMFP-LD) and a built-in feedback cavity formed by a fiber facet. The results show that two lasing modes with frequency separation of ∼0.58 THz and comparable peak powers can be achieved by judicious adjustment of the bias current and the operating temperature of the laser chip, which has a peak fluctuation of less than ∼1 dBm over a measurement pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…When the injection power is linearly increased or reduced, the threshold varies, and it is dependent on the optical injection frequency. A similar phenomenon can also be observed in Fabry-Pérot laser diodes [18].…”
supporting
confidence: 74%
“…When the injection power is linearly increased or reduced, the threshold varies, and it is dependent on the optical injection frequency. A similar phenomenon can also be observed in Fabry-Pérot laser diodes [18].…”
supporting
confidence: 74%
“…The bistability hystereses corresponding to dominant modes are clearly visible, while the hysteresis corresponding to the side mode is somewhat degraded, which might be the consequence of the SL's sensitivity on current intensity and temperature fluctuations [29]. Although this work focuses on the demonstration of the bistability effect in sophisticated laser design, it does not provide an insight into the mechanism of wavelength switching, nor estimate of the switching time between the hysteresis branches.…”
Section: Introductionmentioning
confidence: 96%
“…A recent experimental study of the dual mode FP-LD, based on the built-in external cavity [29], has demonstrated that the bistability of the two dominant modes can be achieved by injecting the light from the ML into one of the suppressed side modes situated between the two dominant modes, and further controlled by the wavelength detuning from this side mode. The bistability hystereses corresponding to dominant modes are clearly visible, while the hysteresis corresponding to the side mode is somewhat degraded, which might be the consequence of the SL's sensitivity on current intensity and temperature fluctuations [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, the coherency of these lasers is a vital issue to obtain a reduced phase noise of the system. Subsequently, various existing approaches to further improve the performance of these configurations have been reported; for instance, external optical injection [11], side mode injection [12], self-injection [13], etc.…”
Section: Introductionmentioning
confidence: 99%